New treatment for nipple soreness in breastfeeding mothers: A clinical trial study - Reza Saeidi; Mahin Tafazoli; Mahboobeh Gholami; Reza Mazloom (Mashhad University of Medical Sciences, 2015)
Background: A common, early postpartum concern of the breastfeeding mother is nipple pain. Because of a lack of effective treatment and opposing results about lanolin, we decided to compare the effect of lanolin ointment and aloe Vera gel on nipple soreness treatment. Methods: This clinical blind trial was performed in Mashhad, Iran, from February 2008 to May 2009. Sampling was nonrandom and purposive, and then samples were divided randomly into two groups. After first applying the preparation on their arms to check for allergy symptoms, mothers were instructed to then rub the preparation on their nipples three times a day for seven consecutive days, each application performed after feeding the baby. Mothers were to let the preparation dry and not to wash it before the next feeding. Researcher pretreatment at the third and seventh day filled out the Storr scale with interviews and examinations. There were no complications in mothers and infants because of the drug's usage The data was then analyzed with Spss 11.5 and Mann-Whitney, Student's t-test, and t-paired tests. Results: A total of 100 samples enrolled with 50 samples in the lanolin group and 50 samples in the aloe vera group. In aloe Vera group Nipple soreness scoring decreased significantly at the third day versus pretreatment (p=0.00) and also at the seventh day versus pretreatment and the third day (p=0.000). Nipple soreness scoring decreased significantly at the third day versus pretreatment (p=0.00) and also at the seventh day versus pretreatment and the third day (p=0.000, p=0.001). The two groups were homogenous at the pretreatment day (p=0.711), but there was a significant difference between the two groups at the third and seventh day (p=0.048, p=0.003). Conclusion: Aloe Vera is more effective than lanolin on nipple soreness healing.